Some new records and one new species of the genus Lebertia Neuman (Acari: Hydrachnidia: Lebertiidae) from Turkey - Esen, Yunus; Erman, Orhan (Tubitak Scientific & Technological Research Council Turkey, 2015)
In this study, water mites of the genus Lebertia Neuman, 1880 (Acari: Hydrachnidia) collected from Antalya, Artvin, Bingol, Erzurum, Kahramanmaras, and Siirt provinces of Turkey are presented. In total, 12 species were determined. Of these, Lebertia (s. str.) marasensis sp. nov. is described as new to science, while L. (s. str.) rufipes Koenike, 1902; L. (Pilolebertia) longiseta Bader, 1955; L. (Pilolebertia) pilosa Maglio, 1924; L. (Mixolebertia) separata Lundblad, 1930; and L. (Brentalebertia) minutipalpis K. Viets, 1920 are new records for the Turkish fauna.
Keywords: Water mites; new records; Hydrachnidia; Lebertiidae; Lebertia; Turkey